Thermal analysis of LiFePo4 batteries during rapid charge with evaporative cooling system - Mollik, Md. Sazib; Rashid, Muhammad Mahbubur; Rahman, Mohammed Ataur (Inderscience Enterprises Ltd, 2021)
The development of rapid charging mechanism for LiFePo4 batteries is one of the key concerns for electric vehicles. The main drawbacks of LiFePo4 battery charging are overcharge, overcurrent, and high temperature which affects longevity, efficiency, and battery life cycle. The effect of the battery’s internal temperature on the rapid charging process has been investigated. Firstly, the CC-CV charging method is applied for rapid charging to analyse the internal temperature. Then, develop a thermal management system to enhance the battery charging performances by maintaining the lowest level of raised temperature. Experimental results have shown that the Refrigerant-134a based cooling system is capable to maintain battery temperature within the range of 20°C–40°C. Without any cooling system, the charging temperature is recorded as 54.12°C which is higher than the reference temperature. With the designed cooling mechanism, the evaporator surface average temperature and battery average temperature are measured as 14°C and 25°C, respectively.